Memorandum on the Sterling Assets of the British Colonies: A Comment - Hazelwood, Arthur (Review of Economic Studies, 1954)
Journal Article Memorandum on the Sterling Assets of the British Colonies : A Comment Get access Arthur Hazlewood Arthur Hazlewood Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 1, 1954, Pages 72–74, https://doi.org/10.2307/2296228 Published: 01 January 1954